Randomized controlled trial of magnesium sulphate in severe closed traumatic brain injury - Dhandapani, SS; Gupta, Aditya; Vivekanandhan, S; Sharma, BS; Mahapatra, AK (Indian Journal of Neurotrauma, 2008)
Magnesium decline is likely to play an important role in the pathogenesis of Traumatic Brain Injury (TBI). This study was undertaken to test the therapeutic efficacy and safety of parenterally administered Magnesium sulphate (MgSO4) in patients of severe closed TBI. Adult patients admitted within 12 hours of closed TBI with Glasgow coma score 5 to 8 fulfilling eligibility criteria were randomized to two groups, one group receiving ‘standard care’ and the other, MgSO4 in addition as per the Pritchard regimen. The outcome measures were Glasgow outcome scale at 3 months and other relevant clinical parameters. Seventy patients were randomized after obtaining informed consent, and 30 in each group remained in the study till 3 months. Favorable outcome was observed in 22 out of 30 patients (73.3%) who had received MgSO4, as compared with 12 out of 30 (40%) in control group. Univariate analysis revealed an odds ratio (OR) of 4.13 (95% CI 1.39–12.27) and the P value was 0.009. In the logistic regression analysis, the adj. OR was 4.24 (95% CI 1.1–16.36) and the P value was 0.036. The secondary outcomes analyzed in MgSO4 group showed significant difference with respect to intra-operative brain swelling at the end of surgical decompression and mortality at 1 month. No significant adverse effects were observed. Parenteral MgSO4 appears to have some favorable influence on mortality and intra-operative brain swelling without any significant adverse effects.
Keywords: Severe traumatic brain injury; Magnesium sulphate; Pritchard regimen; Outcome